A revised geographical range for Liolaemus elongatus Koslowsky, 1896 (Squamata: Liolaemini) in Argentina: review of reported and new-data based distribution with new localities - Minoli, Ignacio (2013)
Estimating the effective geographical ranges of species is central to species-oriented conservation and management. In this paper, we review the geographical distribution of Liolaemus elongatus Koslowsky, 1896 with three new records for northern Chubut and southern Río Negro provinces, Argentina. Based on detailed locality records pooled from multiple data sources, including new records obtained for this study, we revise the range of L. elongatus sensu stricto and provide geographical distribution maps comparing the previously recognized range to that proposed herein. Our results show that L. elongatus possesses a much more limited geographic distribution than previously thought, being restricted to areas south of 38°S latitude; the newly proposed range is merely half the species formerly recognized geographical distribution.